What is the Relationship Between Self-Awarenes and Learning Achievement students? - Wardana, Mochammad Ichsan; Azizah, Nurul; Makhbuloh, Deden; Farida, Farida; Octafiona, Era (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This research examines the relationship between Self-Awareness and learning outcomes in the Aqidah Akhlak subject at MTs Daarul Ma'arif Tegineneng. This study was motivated by pre-research data which showed an understanding of students' Self-Awareness, with several aspects such as independent attitudes (4%), skills in expressing thoughts (14%), and the ability to recognize feelings (14%) which still require development. The research used a quantitative approach with an ex-post facto design, involving a population of 144 class VIII students used in four parallel classes. The research sample was determined using the Slovin formula with a margin of error of 10%, resulting in 59 respondents selected using a simple random sampling technique. Data were analyzed using normality tests, linearity tests, and hypothesis tests including T tests, F tests, and coefficient of determination. The research results show that although Self-Awareness has a significant effect on learning outcomes (significance value 0.001), its contribution is relatively small, only 1.1%. Other factors that were not researched, such as motivation and learning methods, are more dominant in influencing student learning outcomes. Nevertheless, Self-Awareness still plays an important role in supporting learning outcomes, and therefore, it is recommended that schools develop programs to increase students' Self-Awareness as part of efforts to support their learning success. Further research needs to be carried out to explore other factors that influence student learning outcomes.